BEHAVIOURAL SCIENCES AT UNIVERSITY OF HEALTH SCIENCES: THE WAY FORWARD - Khan, Junaid Sarfraz; Mukhtar, Osama; Tabasum, Saima (Journal of Ayub Medical College Abbottabad, 2016)
Background: The association of medical ethics with teaching and training and health profession has been informal, largely dependent on role modelling and the social contract of the physicians with the community that they abide by. This study was conducted to examine the effect, if any, of introducing the subject of Behavioural Sciences on students’ performance in the clinical years’ ’˜viva voce’ and ’˜patient interactions’ components of the examinations. Methods: A prospective study on four cohorts of students at UHS from 2007 to 2012 (8,155 candidates). Reliability was calculated through Cronbach’s Alpha. Linear Regression Analysis was applied to determine the relationship between the scores of Basic Medical Sciences, Behavioural Sciences and Forensic medicine with the viva voce and Structured Stations marks of the Clinical Sciences in OSCE. Gender and demographics analysis was also done. Results: Cronbach’s Alpha was 0.47, 0.63, 0.67 and 0.53 for the Papers of Behavioural Sciences from 2007 to 2010 respectively. Poor predictive value of Behavioural Sciences for performance in the clinical years’ viva voce and OSCE was identified. Basic Medical Sciences and Forensic Medicine were statistically significant predictors for the performance of female candidates in all four cohorts of the study (p<0.05). In Central Punjab, Behavioural Sciences statistically significantly predicted for better performance in all four cohorts of the study (p<0.05). Conclusion: It is premature to understand the results of Behavioural Sciences teaching at University of Health Sciences (UHS). We can still safely conclude that it can only have a positive sustained effect on the healthcare delivery systems and patient care in Pakistan if it is integrated within each subject and taught and learned not as a theoretical construct but rather an evaluation of one’s values within the code of conduct of medical professionalism in the larger context of the societal and cultural norms.